Selective alterations of neurons and circuits related to early memory loss in Alzheimer's disease - Llorens-Martín, María; Blazquez-Llorca, Lidia; Benavides-Piccione, Ruth; Rabano, Alberto; Hernandez, Felix; Avila, Jesus; DeFelipe, Javier (Frontiers in Neuroanatomy, 2014)
A progressive loss of episodic memory is a well-known clinical symptom that characterizes Alzheimer’s disease (AD). The beginning of this loss of memory has been associated with the very early, pathological accumulation of tau and neuronal degeneration observed in the entorhinal cortex (EC). Tau-related pathology is thought to then spread progressively to the hippocampal formation and other brain areas as the disease progresses. The major cortical afferent source of the hippocampus and dentate gyrus is the EC through the perforant pathway. At least two main circuits participate in the connection between EC and the hippocampus; one originating in layer II and the other in layer III of the EC giving rise to the classical trisynaptic (ECII→dentate gyrus→CA3→CA1) and monosynaptic (ECIII→CA1) circuits. Thus, the study of the early pathological changes in these circuits is of great interest. In this review, we will discuss mainly the alterations of the granule cell neurons of the dentate gyrus and the atrophy of CA1 pyramidal neurons that occur in AD in relation to the possible differential alterations of these two main circuits.